Tax Competition with Intermunicipal Cooperation - David R. Agrawal; Marie-Laure Breuillé; Julie Le Gallo (CESifo GmbH, 2024)
We study local tax competition when municipalities can voluntarily cooperate. We compare the intensity of interjurisdictional policy interdependence between competing municipalities within the same “establishment for inter-municipal cooperation” (EIMC) and competing municipalities outside of the cooperative unit. To resolve the endogeneity of the decision to cooperate we apply the approach of Kelejian and Piras (2014). The strategic response to the average tax rate among peer members of the same EIMC is less intense than the response to the average tax rate of municipalities outside of the cooperative unit. A one percentage point decrease in the average tax rate of non-members lowers the own-jurisdiction tax rate by 0.58 percentage points, while a one unit decrease in the tax rate of towns within the EIMC lowers the own-jurisdiction rate by 0.31 percentage points. Our empirical methods can be used to study strategic interactions within other cooperative groups, including supra-national institutions such as the European Union.
Keywords: C20; H20; H70; R50; 330; tax competition; intermunicipal cooperation; spatial autoregressive models; endogenous weight matrix; local public finance; networks